Lessons Learned on the Activities of the Psychological Healing Community Applied Brain Science Concept Among the Health Care Practitioners: The Pilot Study of the Community Hospitals in Pattani Province - Keawpimon, Preeya; Reungrit, Rattikarn; Noypha, Watcharee (Princess of Naradhiwas University Journal, 2021)
This case study research aimed to describe the lesson learned on the activities of the psychological healing community applied brain science concept among the health care practitioners of the community hospitals in Pattani province. Purposive sampling was used to selected two community hospital, and snowball sampling was use for selected the informants. Twenty informants included nurses, pharmacists, physicians, Thai traditional medicine practitioners, and health care volunteers. The research implemented from October 2018 to December 2019. Data were collected by focus group and analyzed by content analysis. The results found three essential lessons learned included 1) activities applied brain science helped to promote mental health among health care practitioners, 2) essential activities of healing community for health care practitioners included alternative health care, managed working environment to promote relaxation, and empowering course training, and 3) learning organization of healing community for health care practitioners needed transformative leader. The research result revealed the activity model to care for health care practitioners in need of psychological care which can be adapt to community hospital in the unrested areas.